Pathogenetic Factors and Mechanisms of Development of Acute Ischemic Type Cerebral Circulation in Young People (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The article analyzes the literature sources covering the results of the study of causative factors and pathogenetic mechanisms of the development of ischemic stroke in young people. Cerebral factors, the influence of homocysteine and neurotrophins on the course, clinical manifestations and outcome of the disease were studied. Knowledge of all macro- and microstructural cerebral factors will make it possible to determine the criteria for choosing the most optimal treatment, prevent the development of possible complications, and develop an algorithm for rehabilitation measures.